PERSOALAN WANITA KARIR DAN ANAK DALAM KELUARGA PEGAWAI NEGERI SIPIL (PNS) DI PROVINSI JAMBI - Samsu Samsu (Harakat an-Nisa: Jurnal Studi Gender dan Anak, 2020)
This article aims to identify problems of career women at work whether because of economic factors or because of social status. This study shows the variables associated with:1) the legth of employment, 2) reasons of work because of economic incentives, and 3) the views of career to career women. There are 30 civil servants as a career women spread in 11 regencies/cities in Jambi Province used as a sample in this study. This study uses a simple quantitative research. Data were analyzed using mean and standard deviation. As overall, the results showed that studies have shown that although the career women who worked who worked as a civil servant in Jambi Province has a service life that is long enough, that over five years, but the ,otive for their work as the career women not because of economic incentives (mean =2.50; it’s a low interpretation). This is reinforced by the views of career to civil servant which they pursue are at the simple stage (mean =2.88). because of that, it can be concluded and identified that the issue of career women in a career for civil servants in Jambi Province, not because of economic problems. Allegedly because of issues of social status that requires them to work, although the issue of social status is not to be studied in this research.